Supplementary dataset to the article "Effects of ivermectin, long-acting ivermectin and moxidectin excreted by cattle on dung fauna, especially on Onthophagus hirculus beetle under field conditions in Argentina western´s pampas." [Conjunto de datos] - Suarez, Victor Humberto (Instituto Nacional de Tecnología Agropecuaria (INTA), 2025)
EEA Salta